Upaya Peningkatan Minat Belajar Fisika untuk Siswa SMA Melalui Praktikum Menggunakan Aeronautics Mobile Laboratory - Arifin, Mufti; Yuniarti, Endah; Fairuza, Syarifah; Freddy Franciscus (Universitas Dirgantara Marsekal Suryadarma, 2024)
Community Service Activities (PKM) carried out by the Aeronautics Engineering Study Program, Air Marshal Suryadarma University use the Aeronautics Mobile Laboratory in the form of physics practicum. PKM aims to increase high school students' interest in physics lessons. The practicum was held at SMA 11 Bekasi on October 31 2023 with the moving student concept, namely a group consisting of 4 students carrying out observations and experiments alternately on 10 choices of physics material related to aeronautics technology (wind tunnel, Coanda effect, venturi pipe, honeycomb structure, paper planes, impacts, hollow plates, pleated structures, resonance, and vibration). Groups of students move from one practical table to another. After the activity, students were given a questionnaire to measure changes in student interest in physics lessons. The questionnaire results showed that the PKM objectives were successful with 81% of participants stating that their interest in physics lessons had increased after participating in the Aeronautics Mobile Laboratory practicum activities. However, improvements still need to be made so that the time allocated for each practical module is sufficient and the participant group can experience all types of practical modules.